THEORY OF ARGUMENTATION IN FINANCIAL MARKETS - ESTRADA, Fernando (Journal of Advanced Studies in Finance, 2010)
This paper aims to explore the relevance of the Theory of Argumentation TA in the complex area of financial reporting. Specifically, we investigated the scope of the phenomenon of persuasion in advertising. It examines advertisements in publications notable economic movement in Colombia. The financial communication is important to distinguish how to run the models of behavior based on beliefs of agents. Consequently, investors' beliefs can also change systematically with changes in market prices. This paper is the first part and its purpose is to prepare from the Theory of Argumentation TA an application to the financial sector in Colombia.